Pharmacological properties of centella asiatica hydrogel in accelerating wound healing in rabbits - Afnan, Sh. Ahmed; Muhammad, Taher; Mandal, Uttam K.; Juliana, Md Jaffri; Deny, Susanti; Mahmood, Syed; Zainul Amiruddin, Zakaria (BioMed Central Ltd., 2019)
Background: Various extracts of Centella asiatica (Apiaceae) and its active constituent, asiaticoside, have been reported to possess wound healing property when assessed using various in vivo and in vitro models. In an attempt to develop a formulation with accelerated wound healing effect, the present study was performed to examine in vivo efficacy of asiaticoside-rich hydrogel formulation in rabbits. Methods: Asiaticoside-rich fraction was prepared from C. asiatica aerial part and then incorporated into polyvinyl alcohol/polyethylene glycol (PVA/PEG) hydrogel. The hydrogel was subjected to wound healing investigation using the in vivo incision model. Results: The results obtained demonstrated that: i) the hydrogel formulation did not cause any signs of irritation on the rabbits’ skin and; ii) enhanced wound healing 15% faster than the commercial cream and > 40% faster than the untreated wounds. The skin healing process was seen in all wounds marked by formation of a thick epithelial layer, keratin, and moderate formation of granulation tissues, fibroblasts and collagen with no fibrinoid necrosis detected. Conclusion: The asiaticoside-rich hydrogel developed using the freeze-thaw method was effective in accelerating wound healing in rabbits.